Countering Islamophobia through Webcomics on Instagram - Fawzy, Dwimay; A.Manaf, Aini Maznina; Tengku Azzman, Tengku Siti Aisha (2021)
The widespread use of social media is directly proportional to the widespread practice of spreading Islamophobia in the digital realm, especially in Western societies whose understanding of Islam or Muslims is primarily based on negative media stereotypes. Various efforts were made, including from Muslim groups who counter against these negative stereotypes through social media and form of counter-narrative. One of them is the Instagram account @yesimhotinthis, which conveys a message about countering Islamophobia from an Egyptian-American Muslim perspective through the format of autobiographical webcomics. The approach taken is different from mainstream comics, which are mostly superhero themed. This study analyses how countering Islamophobia is represented and how Instagram is used to counter Islamophobia. Using Stuart Hall’s Representation Theory as a theoretical framework, this study conducts a content analysis of seven webcomics of @yesimhotinthis Instagram. The results indicated that representation of countering Islamophobia is more emphasized on the aspect of equality and highlighting similarities between Muslims and non-Muslims in social aspects. In addition, Instagram is utilized by adjusting the relations between webcomics and its captions, giving the impression that although Islamophobia is countered in a casual way, it is still a serious problem. The implications of the study on the representation theory are also discussed.